Persepsi Mahasiswa Calon Guru Biologi terhadap Potensi dan Tantangan Penggunaan Artificial Intelligence (AI) dalam Pembelajaran Biologi - Syaleha, Selvi; Fernando, Adam; Nevrita (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
The use of Artificial Intelligence (AI) in education had been widely recognized and applied in various learning contexts. However, among biology teacher candidates, there were still differences in perception regarding its implementation. Some students perceived AI as an innovation that facilitated the learning process, while others believed that its use could lead to dependency and weaken critical thinking skills. Based on these conditions, this study aimed to determine the perceptions of biology teacher candidates regarding the challenges and potential of using Artificial Intelligence (AI) in biology learning. This research was conducted in July 2025 using a quantitative approach with a descriptive research method. The population consisted of all active students of the Biology Education Study Program, Faculty of Teacher Training and Education, Raja Ali Haji Maritime University. The sampling technique employed was purposive sampling, resulting in a total of 170 respondents. The data were collected using a closed questionnaire and analyzed quantitatively through a descriptive approach. The results showed that the overall perception of biology teacher candidates toward the use of AI in biology learning was in the good category, with an average percentage of 58%. These findings indicated that students generally had a positive view of AI utilization as a supportive learning tool, although further reinforcement was still needed in understanding and practical application. This study implied that the integration of AI could contribute to the development of technology based biology learning strategies, particularly in enhancing the effectiveness, creativity, and quality of the learning process. In addition, the results contributed to the enrichment of scientific studies on AI integration in biology education and served as a foundation for future in depth research.